Impact of Entrepreneurial Leadership on Teacher Creativity: The Mediating Role of School Culture in Indonesian Public Senior Secondary Schools - Machali, Imam; Murfi, Ali; Yani, Zhou (MyResearch ID Publishing, 2024)
Purpose – This study explores the relationship between entrepreneurial leadership, school culture, and teachers' creativity within public senior secondary schools in Yogyakarta, Indonesia. The research aims to determine whether entrepreneurial leadership directly influences teacher creativity or whether its impact is mediated through the school culture. Methods/Design/Approach – A quantitative survey methodology was employed, collecting data from 136 teachers across multiple schools in Yogyakarta. Structural Equation Modelling Partial Least Squares (SEM-PLS) was used to analyze the relationships between the variables, including entrepreneurial leadership, school culture, and teachers' creativity. Findings – The results reveal that entrepreneurial leadership does not directly enhance teachers' creativity within the studied context. However, entrepreneurial leadership significantly contributes to a conducive school culture, which in turn positively impacts teachers' creativity. The study identifies school culture as a critical mediator, suggesting that the influence of entrepreneurial leadership on creativity is indirect and operates primarily through the development of a supportive environment. Originality/Value – This study provides new insights into the applicability of entrepreneurial leadership in educational settings, particularly in Indonesia. It challenges the assumption that entrepreneurial leadership directly fosters creativity and underscores the importance of school culture as a mediator. Practical Implications – The findings emphasize the importance of developing a supportive school culture to foster creativity among teachers. Educational leaders should focus on building environments that encourage innovation, collaboration, and growth. Policymakers can support this by integrating entrepreneurial leadership practices with strategies to cultivate a positive school culture, enhancing overall teacher creativity and effectiveness. Keywords Entrepreneurial leadership, school culture, teacher creativity, educational leadership, Indonesian schools. Paper type Research paper